Pneumonia and influenza: specific considerations in care homes - Gordon, Adam; Ewan, Victoria (Cambridge University Press, 2010)
This review provides an update on current evidence surrounding epidemiology, treatment and prevention of lower respiratory tract infection, with special reference to pneumonia and influenza, in care home residents. The care home sector is growing and provides a unique ecological niche for infections, housing frail older people with multiple comorbidities and frequent contact with healthcare services. There are therefore considerations in the epidemiology and management of these conditions which are specific to care homes. Opportunities for prevention, in the form of vaccination strategies and improving oral hygiene, may reduce the burden of these diseases in the future. Work is needed to research these infections specifically in the care home setting and this article highlights current gaps in our knowledge.